2005
DOI: 10.1186/ar1827
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Previous studies have reported that mesenchymal stem cells (MSC) may be isolated from the synovial membrane by the same protocol as that used for synovial fibroblast cultivation, suggesting that MSC correspond to a subset of the adherent cell population, as MSC from the stromal compartment of the bone marrow (BM). The aims of the present study were, first, to better characterize the MSC derived from the synovial membrane and, second, to compare systematically, in parallel, the MSC-containing cell populations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(66 citation statements)
references
References 40 publications
2
63
0
1
Order By: Relevance
“…Cells from regenerated cartilage were spherical, but assumed spindle shape after 7-day culture, whereas cells from regenerated bone maintained their initial spindle shape. Activin A, a marker preferentially expressed by bone marrow cells,37 showed little expression in cells from regenerated cartilage, but was robustly expressed in cells from regenerated bone (webappendix p 6). Furthermore TGFβ3 recruited a remarkable number of mesenchymal stem or progenitor cells and synovium stem or progenitor cells in vitro by comparison with spontaneous cell migration (webappendix p 7).…”
Section: Discussionmentioning
confidence: 99%
“…Cells from regenerated cartilage were spherical, but assumed spindle shape after 7-day culture, whereas cells from regenerated bone maintained their initial spindle shape. Activin A, a marker preferentially expressed by bone marrow cells,37 showed little expression in cells from regenerated cartilage, but was robustly expressed in cells from regenerated bone (webappendix p 6). Furthermore TGFβ3 recruited a remarkable number of mesenchymal stem or progenitor cells and synovium stem or progenitor cells in vitro by comparison with spontaneous cell migration (webappendix p 7).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other reports claim that CD34 and CD62 are not expressed by MSCs [11,33,34]. Additional antigens that are recognized as markers of progenitors of the marrow stromal cells are CD166, CD105, CD73, and CD63 [34][35][36][37][38][39]. CD166, activated leukocyte cell adhesion molecule (ALCAM), and osteopontin are also involved in MSC-niche interactions [40][41][42][43].…”
Section: Structure and Components Of Stem Cells' Nichementioning
confidence: 93%
“…One documented mechanism by which S-MSC can display their suppression effect on T cells is via the production of IDO 39 (Figure 2, A). It has been shown that S-MSC and BM-MSC can display similar IDO activity at a basal level or when induced by IFN-γ and TNF-α 39 . Therefore, a similar inhibitory effect by S-MSC could be expected on other immune cells.…”
Section: Immunomodulatory Capacity Of Healthy S-msc and Flsmentioning
confidence: 99%